Work and migration : life and livelihoods in a globalizing world - Sørensen, Ninna Nyberg; Olwig, Karen Fog, 1948- (Transnationalism. Routledge research in transnationalism ;, 2003)
Using case studies from those who have moved either transnationally or within their own country, international contributions offer various definitions of what it means to make a living on the move.